Reproductive physiology of caseous lymphadenitis in Katjang does following intradermal infection with Corynebacterium pseudotuberculosis - Abdul Latif, Nur Amirah (2015)
Corynebacterium pseudotuberculosis is the etiological agent for zoonotic caseous lymphadenitis (CLA). CLA is a zoonotic disease with high prevalence in sheep and goats worldwide in chronic and subclinical forms. CLA cause high financial loss to CLA endemic countries due to the condemnation of affected carcasses, reproductive problems, decreased in milk and meat production, poor wool growth and mortality in goats, sheep and other small ruminants. Therefore, the present study aims to examine the presence of C. pseudotuberculosis in reproductive organs and iliac lymph node of non-pregnant does in respect to cellular, hormone and cytokine changes inoculated intradermally in chronic form. This is the first study to review the chronicity of the infection in the reproductive organs and associated lymph node of non-pregnant does. In this study, eighteen non-pregnant healthy Katjang does aged 2 years old were divided randomly into two groups. The first and second group consisted of nine does each and the two groups were subdivided into three subgroups. The first group was experimentally inoculated with 1 ml of 107 cfu of live C. pseudotuberculosis by intradermal route while the second group was given 1 ml of PBS (pH 7) intradermally. The first group was further subdivided into three subgroups where the first subgroup (B1) was kept for 30 days post infection, the second subgroup (B2) was kept for 60 days post infection and the third subgroup (B3) was kept for 90 days. The second group was further subdivided into three subgroups (C1, C2, C3) where they were kept for 30, 60 and 90 days post infection respectively. During the post challenged periods, the goats were observed for clinical signs and blood samples were collected at predetermined intervals for three consecutive months for further analyses. Three goats from the treatment group were sacrificed monthly and post mortem examination was performed and reproductive organs and associated lymph nodes were collected for histopathology. Isolation and identification of C. pseudotuberculosis and PCR were conducted. Results showed there was successful isolation of C. pseudotuberculosis from reproductive organs and iliac lymph nodes of the experimental does after the second month from one of the infected does whereas the other two does only showed positive isolation from the ovary. For the second and third month of post-infection, all infected does showed positive C. pseudotuberculosis in the iliac lymph nodes and all reproductive organs. The concentration of IL-1β and IL-6 increased after three month post-inoculation. Whereas, the hormonal response in the challenged does showed a decrement pattern in progesterone concentration and increment pattern for estradiol hormone throughout three month post-infection. The changes in the hormonal concentration were further supported with the changes in the tissues of reproductive organs in the challenged does. The histopathology of exposed group showed mild to severe inflammatory cells, congestion, degeneration and necrosis in all the reproductive organs and iliac lymph nodes in all treated groups. Iliac lymph node showed moderate inflammatory cells (1.6±0.00), mild congestion (1.0±0.45), moderate degeneration and necrosis (1.5±0.00) for one month post-infection group. In the second month postinfection group, iliac lymph node revealed the presence of moderate inflammatory cells (1.6±0.21), mild congestion (1.2±0.18) and moderate degeneration and necrosis (1.5±0.22). For the treatment group of three month post-infection, the iliac lymph node exhibited the presence of moderate inflammatory cells (1.6±0.22), moderate congestion (1.5±0.11), severe lesion degeneration and necrosis (2.6±0.22). In the treated group of one month post-infection showed mild infiltration of inflammatory cells (1.4±0.00), mild congestion (1.4±0.55), mild degeneration and necrosis (1.4±0.55) of the ovary. In the treated group of second month post-infection, the ovary exhibited mild inflammatory cells (1.4±0.18), mild congestion (1.4±0.26) and mild degeneration and necrosis (1.4±0.18). The third month post-infection group, ovary showed with moderate degeneration and necrosis (2.4±0.15), moderate inflammatory cells (2.3±0.17) and mild congestion (1.4±0.19). In the first groups of one month post-infection, the vagina showed mild inflammatory cells (0.6±0.45), moderate congestion (1.5±0.55) and severe degeneration and necrosis (2.6±0.45). The second month post-infection group revealed vagina with moderate congestion (1.5±0.21), severe degeneration and necrosis (2.5±0.22) and mild inflammatory cells (0.9±0.08). The third month group, the vagina exhibited moderate inflammatory cells (1.5±0.22), severe congestion (2.6±0.22), and severe degeneration and necrosis (2.6±0.22). The uterine horn in the first groups of one month post-infection animals showed mild inflammatory cells (1.4±0.00), moderate congestion (1.9±0.00) and mild degeneration and necrosis (1.3±0.00). In the second month post-infection group, the uterine horn exhibited mild degeneration and necrosis (1.4±0.19), moderate congestion (2.3±0.13) and mild inflammatory cells (1.4±0.21). For the third month post-infection, the uterine horn showed mild degeneration and necrosis (1.3±0.21), moderate inflammatory cells (1.9±0.04) and moderate congestion (2.2±0.06). The uterus of the first month post-infection group showed mild inflammatory cells (1.2±0.00), mild congestion (0.8±0.45) and mild degeneration and necrosis (1.4±0.45). For the second month post-infection group, the uterus showed mild inflammatory cells (1.0±0.04), mild congestion (1.1±0.13) and mild degeneration and necrosis (0.5±0.22). For the third month post-infection group, the uterus exhibited moderate congestion (1.5±0.22), moderate inflammatory cells (1.6±0.22) and moderate degeneration and necrosis (1.5±0.22). For cervix, the first month post infection group showed presence of mild inflammatory cells with mean score of 1.2±0.45, mild congestion with mean score of 1.4±0.33 and mild degeneration and necrosis with mean score of 0.5±0.45. For the second month post-infection group, cervix showed cellular changes of mild inflammatory cells with mean score of 1.0±0.00, mild congestion with mean score of 1.1±0.13, and mild presence of degeneration and necrosis with mean score of 0.8±0.19. For the third month post-infection group, cervix exhibited cellular changes of mild congestion with mean score of 1.1±0.07, moderate inflammatory cells with mean score of 1.5±0.22 and moderate degeneration and necrosis with mean score of 1.5±0.22. In conclusion, PCR and histopathology of the reproductive tract of Katjang does proved that C. pseudotuberculosis can successfully ascended the reproductive tract and penetrated the physical barrier of the genital tract causing severe lesions as observed in this study. The presence of C. pseudotuberculosis causes the IL-1β, IL-6 and estradiol to be increased while progesterone hormone to be decreased gradually.